Chilean labor market efficiency: an earning frontier approach - Salas, Sergio; Contreras, Dante (Estudios de Economía, 2016)
In this paper, we use the econometric frontier approach to estimate efficiency measures of the transformation of human capital into earned income in the Chilean labor market for the period 1957-1998. We find that the mean efficiency is 75%, and that it has been imporving over time. We also find evidence of detrimental effects of non market oriented governments on these efficiency measures. Some evidence is also founded about the effects of health on efficiency, the existence of labor market segmentation and the importance of ""social networks"". Finally we calculate correlation measures and causality tests between the estimated efficiencies and the rate of growth of GDP, finding a statistical precedence of the later to the former. We give then an eppealing explanation for this results.